PENGARUH PENERAPAN PEMBELAJARAN AKTIF TIPE THE POWER OF TWO TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 9 PADANG - Vitriani, Yola; Harisman, Yulyanti; Pratiwi, Merina (STKIP PGRI Sumbar, 2014)
ABSTRACTThis research was conducted due to the studentsâ less confident in expressing their ideas and answering questions given. In addition, the students having low ability had less interest in searching for information and asking questions to those who had higher ability. This research was aimed at revealing whether the mathematics conceptual understanding of the students taught by using The Power of Two active learning strategy was better than that of students taught by using conventional learning. This research is experimental research which research design is randomized on subject. Â Population is student in the class VIII SMPN 9 Padang. The instrument used is examinations with reliabiliti 0,73. Based on the result of data analysis it was found that the value of tcalculated 5,34 was higher than ttable 1,645 with Î± = 0,05, so it can concloded that mathematical conceptual understanding abilityÂ by using The Power ofÂ Two strategy is better than studentâsÂ by using conventional learning in class VIII of SMPN 9 Padang